A new modeling technique based on performance data for photovoltaic modules and horizontal axis wind turbines. Issue 3 (June 2018) - Sharaf Eldean, Mohamed A; El Shahat, Adel; Soliman, AM
This article proposes new methods of modeling and simulation of photovoltaic and horizontal wind turbine systems. The photovoltaic and horizontal wind turbines are modeled by the use of actual data sheets listed in the lookup table model. Moreover, artificial neural network numerical technique is used to simulate and evaluate the designed systems. The implemented work may help the designer and investor to elect a specified photovoltaic module and/or the horizontal wind turbine according to the demanded power load, thence predicting the operating conditions before the establishment process. The results show good matching with the actual data for the photovoltaic and horizontal wind turbine systems.